Accumulation of histone deacetylase 6, an aggresome-related protein, is specific to Lewy bodies and glial cytoplasmic inclusions - Miki, Yasuo; Mori, Fumiaki; Tanji, Kunikazu; Kakita, Akiyoshi; Takahashi, Hitoshi; Wakabayashi, Koichi (Neuropathology, 2011)
Histone deacetylase 6 (HDAC6) plays a crucial role in aggresome formation, resulting in the clearance of misfolded proteins. Previous studies have shown that HDAC6 is concentrated in Lewy bodies (LBs) in Parkinson's disease (PD) and dementia with LBs (DLB) (Cell 115: 727–738, 2003). We performed immunohistochemical and ultrastructural investigations on the brains of patients with various neurodegenerative disorders. Anti‐HDAC6 antibody faintly immunostained the cytoplasm of neuronal and glial cells in control subjects. In PD and DLB, almost all of the cortical, brainstem‐type and peripheral LBs were intensely immunolabeled with anti‐HDAC6. In multiple system atrophy (MSA), the vast majority of glial cytoplasmic inclusions (GCIs) were also positive for HDAC6. Immunoelectron microscopy revealed that the reaction product was localized to the filamentous structures in LBs and GCIs. Various neuronal and glial inclusions in neurodegenerative disorders other than LB disease and MSA were HDAC6‐negative. These findings suggest that accumulation of HDAC6 is specific to α‐synucleinopathy and that both LBs and GCIs may represent cytoprotective responses to sequester toxic proteins.